Hemicrania Continua: Beneficial Effect of Non‐Invasive Vagus Nerve Stimulation in a Patient With a Contraindication for Indomethacin. Issue 2 (11th November 2016) - Eren, Ozan; Straube, Andreas; Schöberl, Florian; Schankin, Christoph
Abstract : Hemicrania continua (HC) is a primary chronic headache disorder, characterized by a continuous and strictly unilateral headache, with possible cranial autonomic symptoms during episodes of pain exacerbation. The unilateral headache generally responds well to indomethacin; however, continuous indomethacin intake is often not tolerated due to severe adverse effects, like hypertension, gastrointestinal discomfort (especially if combined with aspirin), slightly increased risk of vascular events, and bronchial spasms. Therefore, alternative treatment options are desperately needed. Non‐invasive vagus nerve stimulation (nVNS) has been shown to be effective in patients with cluster headache, another trigeminal autonomic cephalalgia (TAC), with cranial parasympathetic autonomic activation during the attacks.